STUDYING THE COMPOSITION OF COMPLEXES ON THE BASIS OF PALLADIUM(II), COPPER(II), IRON(III) CHLORIDES AND POLYVINYLPYRROLIDONE - Akbayeva D.N.; Seilkhanova G.A.; Bakirova B.S.; Smagulova I.A.; Salkhay Ә.Қ. (Academic Scientific Journal of Chemistry, 2019)
The compositions of polymer-metal complexes based on palladium(II), copper(II), iron(III) chlorides and polyvinylpyrrolidone were established by potentiometric and conductometric methods. The values of the Bjerrum formation functions were calculated. According to the experimental data obtained for determination the composition of the complex, titration curves were constructed and the optimal molar ratios of the reacting components were found. The obtained calculated data indicate the formation of polymeric complexes of palladium and copper, in which one complex-metal ion forms into three compound mono-link of polyvinylpyrrolidone. And in the case of the iron polymeric complex, there is one ion of the complexing metal for the four constituent mono-link of polyvinylpyrrolidone. Coordination saturation of metal complexing agents in these complexes is due to solvent molecules or anion of metal salts. The structure and morphology of the synthesized complexes were studied using IR- spectroscopy and scanning electron microscopy. It has been established that the oxygen atoms of polymeric ligands take part in the formation of a coordination bond with the metal ion. The results of electron microscopy indicate the formation of polymer films of a complex with a porous inhomogeneous amorphous structure.